Chemical targeting of NEET proteins reveals their function in mitochondrial morphodynamics. (12th November 2020) - Molino, Diana; Pila‐Castellanos, Irene; Marjault, Henri‐Baptiste; Dias Amoedo, Nivea; Kopp, Katja; Rochin, Leila; Karmi, Ola; Sohn, Yang‐Sung; Lines, Laetitia; Hamaï, Ahmed; Joly, Stéphane; Radreau, Pauline; et al.
Abstract: Several human pathologies including neurological, cardiac, infectious, cancerous, and metabolic diseases have been associated with altered mitochondria morphodynamics. Here, we identify a small organic molecule, which we named Mito‐C. Mito‐C is targeted to mitochondria and rapidly provokes mitochondrial network fragmentation. Biochemical analyses reveal that Mito‐C is a member of a new class of heterocyclic compounds that target the NEET protein family, previously reported to regulate mitochondrial iron and ROS homeostasis. One of the NEET proteins, NAF‐1, is identified as an important regulator of mitochondria morphodynamics that facilitates recruitment of DRP1 to the ER–mitochondria interface. Consistent with the observation that certain viruses modulate mitochondrial morphogenesis as a necessary part of their replication cycle, Mito‐C counteracts dengue virus‐induced mitochondrial network hyperfusion and represses viral replication. The newly identified chemical class including Mito‐C is of therapeutic relevance for pathologies where altered mitochondria dynamics is part of disease etiology and NEET proteins are highlighted as important therapeutic targets in anti‐viral research. Synopsis: This study identifies the small molecule Mito‐C as an activator of mitochondrial fragmentation. Mito‐C suppresses dengue virus replication by counteracting virus induced mitochondrial fusion. Mito‐C targets the NEET family proteins and stabilizes ER‐mitochondria contact sites. NAF‐1, a NEET family protein, promotes Drp1 recruitment to ER‐mitochondria contact sites and induces mitochondrial fragmentation. Mito‐C promotes DRP1 local recruitment to mitochondria and mitochondrial fragmentation. Mito‐C inhibits dengue virus induced mitochondrial fusion and suppresses viral replication. Abstract : This study identifies the small molecule Mito‐C as an activator of mitochondrial fragmentation. Mito‐C suppresses dengue virus replication by counteracting virus induced mitochondrial fusion.